1984
DOI: 10.1111/j.1365-2125.1984.tb02447.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of specific [3H]‐ouabain binding to different types of human leucocytes.

Abstract: We have studied the specific binding of [3H]‐ouabain to intact mononuclear leucocytes (82% lymphocytes) and polymorphonuclear leucocytes. In both types of cells [3H]‐ouabain binding was saturable, confined to a single site of high affinity, slow to reach equilibrium, slow to reverse, temperature‐dependent, competitively antagonized by potassium, and facilitated by the presence of divalent cations. The equilibrium dissociation constants were 2.4 +/‐ 0.7 nmol/l (polymorphs) and 2.4 +/‐ 0.4 nmol/l (mononuclear ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…As the apparent sensitivity of the HeLa Na', K+-ATPase in short term experiments is similar to that of other types of human cells (heart cell membranes; Erdmann, 1981: leucocytes;Boon et al, 1984); it may well be that the true sensitivity of these other cells is also some 4 to 10 times the apparent value. This sensitivity is such that if this isoform is present in human heart the normal plasma concentrations of cardiac glycosides of a few nm should give a substantial block of the sodium pumps.…”
Section: Apparent Kd In Short Term Experimentsmentioning
confidence: 68%
“…As the apparent sensitivity of the HeLa Na', K+-ATPase in short term experiments is similar to that of other types of human cells (heart cell membranes; Erdmann, 1981: leucocytes;Boon et al, 1984); it may well be that the true sensitivity of these other cells is also some 4 to 10 times the apparent value. This sensitivity is such that if this isoform is present in human heart the normal plasma concentrations of cardiac glycosides of a few nm should give a substantial block of the sodium pumps.…”
Section: Apparent Kd In Short Term Experimentsmentioning
confidence: 68%
“…This could be explained by different potassium permeabilities of the plasma membranes of MNL and PMNL. Uncoupled sodium-efflux in MNL may also be considered as a possible mechanism for the decreased uptake of K+ (86Rb+) by MNL (Glynn & Karlish, 1975 , 1984;Clausen, 1986;Ford et al, 1979). Qualitative differences in the pump units from different tissues may also occur.…”
Section: Discussionmentioning
confidence: 99%
“…The observed rates of pump inhibition reflect a low rate of association of ouabain with pump. Ligand-binding studies with tritiated ouabain have previously demonstrated low rates of association of ouabain with the Na+-K+ pump of human leucocytes at ouabain concentrations of 108mol 1-1 or less (Boon et al, 1984;Pedersen & Klitgaard, 1983). Except for the extreme concentrations of ouabain studied, which caused either no inhibition (10'0°mol 1-l) or an immediately obtained maximal inhibition (105mol L-), a steady-state level of pump inhibition was observed after about 2.5 h incubation of both MNL and PMNL with ouabain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations